2014
DOI: 10.1111/ejn.12697
|View full text |Cite
|
Sign up to set email alerts
|

Frequency matters: beta‐band subthalamic nucleus deep‐brain stimulation induces Parkinsonian‐like blink abnormalities in normal rats

Abstract: The synchronized beta band oscillations in the basal ganglia-cortical networks in Parkinson's disease (PD) may be responsible for PD motor symptoms or an epiphenomenon of dopamine loss. We investigated the causal role of beta band activity in PD motor symptoms by testing the effects of beta frequency subthalamic nucleus deep brain stimulation (STN DBS) on blink reflex excitability, amplitude, and plasticity in normal rats. Delivering 16 Hz STN DBS produced the same increase in blink reflex excitability and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our present and previous work has emphasized the therapeutic potential of STN DBS for the treatment of addiction but has also indicated that the frequency used has to be carefully chosen in order to achieve beneficial outcomes and avoid deleterious effects, as described in PD. In rodents and nonhuman primates, low-frequency stimulations drive STN neurons' activity both in vitro and in vivo (52)(53)(54), which would then alter STN output structure activities to promote or worsen PD-like motor symptoms in preclinical and clinical studies (55)(56)(57)(58). In contrast, high-frequency STN DBS is thought to produce its beneficial effect through inactivation of the STN neurons but also antidromic activation of cortical motor neuron in rodent PD models (51,58).…”
Section: Discussionmentioning
confidence: 99%
“…Our present and previous work has emphasized the therapeutic potential of STN DBS for the treatment of addiction but has also indicated that the frequency used has to be carefully chosen in order to achieve beneficial outcomes and avoid deleterious effects, as described in PD. In rodents and nonhuman primates, low-frequency stimulations drive STN neurons' activity both in vitro and in vivo (52)(53)(54), which would then alter STN output structure activities to promote or worsen PD-like motor symptoms in preclinical and clinical studies (55)(56)(57)(58). In contrast, high-frequency STN DBS is thought to produce its beneficial effect through inactivation of the STN neurons but also antidromic activation of cortical motor neuron in rodent PD models (51,58).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of articles did not stress the pathology examination after experiments and few of them provided the proof of the position accuracy, which could be a potential cause for great deviation, so the data may not be authentic. [ 6 7 ] Considering the current situation, we conclude some factors that may influence the accuracy of the coordinate.…”
Section: Discussionmentioning
confidence: 98%
“…Lowfrequency (23 Hz) STN stimulation in normal rodents and NHPs can also evoke movements similar to human tremor and dyskinesia [96]. Furthermore, low-(7 or 16 Hz) but not highfrequency (130 Hz) stimulation in normal rodents can also evoke similar eye-blink and EMG abnormalities as observed in human dystonia and PD patients [97]. …”
Section: Accepted Manuscriptmentioning
confidence: 94%